ISOLASI DAN IDENTIFIKASI JAMUR-JAMUR PENDEGRADASI AMILOSA PADA EMPELUR TANAMAN SAGU (Metroxylon sagu Rottb.) - Ade, Filza Yulina (Universitas Pasir Pengaraian, 2013)
Some microorganism can be amylose degradation which have large starch component in plant. A research about isolation and identification of fungusdegradation in core of plant sago (Metroxylon sagu Rottb.), had been done using purposive sampling method, isolation and selection of microbes alreadyexisted in sago. This research aimed to look fungus species in core of plant sago which amylose degradation potential and to know can be able in amylose degradation. Result showed that species of fungus have amylose degradation potential. Kinds of fungus isolate which founded are Aspergillus niger,Geotrichum sp., Aspergillus oyzae dan Rhizopus oryzae. All the fungus isolate have good and big potential in amylose degradation with afforded to starch degrade at medium to fast rate.